Expression of the bcl-2 oncogene product and chromosomal translocation t(14;18) in Hodgkin's disease. - Lorenzen, J; Hansmann, M; Hansmann, M; Pezzella, F; Pezzella, F; Hesse, C; Kneba, M; Gatter, K; Gatter, K; Fischer, R; Fischer, R (1992)
The B-cell lymphoma/leukemia oncogene bcl-2 takes part in crucial regulatory events in B-cell maturation and differentiation. The reciprocal chromosomal translocation t(14;18), leading to overexpression of this oncogene, can be found in the majority of follicular lymphomas and much less frequently in B-cell leukemias and diffuse lymphomas. We have studied the expression of this protein in different subtypes of Hodgkin's disease using monoclonal antibodies directed against a formalin-resistant epitope of the bcl-2 protein and also have investigated these cases by polymerase chain reaction for evidence of the t(14;18) translocation. We were particularly interested to determine whether nodular paragranuloma (lymphocyte-predominant, nodular), which differs from other subtypes of Hodgkin's disease by virtue of the B-cell nature of its malignant cell population, is characterized by expression of the bcl-2 protein. Our data indicate that only a small number of nodular paragranulomas express the bcl-2 protein and that the expression is not specific for this type of Hodgkin's disease. In a smaller number of cases this expression of bcl-2 could be explained by the presence of the translocation t(14;18).